MEMBANGUN JIWA KEWIRAUSAHAAN REMAJA MELALUI PEMBUATAN HAND SANITIZER DI MASJID AL-ITTIHAD PERUMAHAN GRIYA MUSTIKASARI KOTA BEKASI - Lili Fadli Muhammad (Institut Bisnis Muhammadiyah Bekasi, 2022)
Preventing the spread of Corona Virus Disease 2019 (Covid-19) is the obligation of every resident in Indonesia. People who live in Griya Mustikasari Housing, Mustika Sari Village, Mustika Jaya District, and Bekasi City also feel obliged to themselves, their families, and the surrounding environment to prevent the spread of Covid-19. One of the efforts made by implementing health protocols when you have to move outside the home. The health protocol that needs to be done is washing hands with hand sanitizer. The need for hand sanitizer needed to wash hands is very large, besides the price of hand sanitizer during the Covid-19 Pandemic is also very expensive. The number of people who wash their hands using a hand sanitizer and the price of hand sanitizer is too high, it can be ascertained that many people are looking for alternatives to get a hand sanitizer easily and at an affordable price. This opportunity needs to be used by the 10C IBM Bekasi Real Work Lecture Group in carrying out the Community Service program to provide training to make hand sanitizer. The short-term goal is for their own consumption, while in the long term they can sell it to residents in Griya Mustikasari Housing who have the potential to need hand sanitizer.